Layoff costs and efficiency with asymmetric information - Alain Delacroix; Etienne Wasmer (Institute for the Study of Labor (IZA), 2009)
Wage determination under asymmetric information generates inefficiencies due to excess turnover. Severance pay and layoff taxes can improve efficiency. We show that inefficient separations can even be fully removed with fixed separation taxes in the case where the relevant private information is exponentially distributed.
urn:nbn:de:101:1-20091105958
Keywords: J41; J60; 330; Bargaining; asymmetric information; employment protection legislation; inefficient job separations; Lohnverhandlungen; Asymmetrische Information; Arbeitsmobilität; Allokationseffizienz; Arbeitnehmerschutz; Abfindung; Kündigungsschutz; Theorie